INTERNALISASI NILAI BUDAYA LOKAL NGADA DALAM KURIKULUM PENDIDIKAN MUSIK SEBAGAI STRATEGI PENGUATAN PENDIDIKAN KARAKTER - Bupu, Anjelina; Canera, Natalia G.; Ruda, Maria V. D.; Goan, Yakobus A. D.; Wonga, Yohana L.; Dhiu, Maria T. (Jurnal Citra Pendidikan, 2026)
This study examines the internalization of Ngada local cultural values in the music education curriculum as a strategy for strengthening character education through a literature review approach. Core values—communal solidarity, respect for ancestors, religiosity, and human–nature balance—remain resilient amid globalization. These values are transmitted through families, customary communities, churches, formal education, and creative cultural practices, and are integrated into traditional music such as Foi Doa and the Ja’i dance. The findings highlight the adaptive function of culture in preserving local identity while responding to global demands. The novelty of this research lies in its integrative analysis that combines cultural, music education, and socio-economic dimensions as an effective strategy for reinforcing the character of young generations.